2018
DOI: 10.24198/pjd.vol30no3.19302
|View full text |Cite
|
Sign up to set email alerts
|

Human age estimation based on pulp volume of canines for chronological age estimation: Preliminary research

Abstract: Introduction: Age estimation has an important role in the process of human identification and needs to be performed in an efficient, fast, and accurate ways. Age estimation based on the pulp cavity volume of canines was referring to the theory stated that the apposition of secondary dentine during human life could be determined as an age indicator. This study was aimed to estimate the human age based on the pulp volume of canines for chronological estimation. Methods: Forty-one canine teeth from Cone Beam Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Some previous studies which evaluated age estimation from the canine's pulp volume in some countries and populations displayed regression models with lower coefficients of determination including studies in France (R 2 varied between 0.32 and 0.47) (Tardivo et al 2011), Indonesia (R 2 = 75.3%) (Hidayat et al 2018), and India (R 2 = 75.5%) (Jagannathan et al (2011), as well as studies in subjects of Pakistani origin (R 2 = 0.33) (Kazmi et al 2019) and Egyptians (pulp volume of mandibular canines) (R 2 = 75.5%) (Elmoazen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies which evaluated age estimation from the canine's pulp volume in some countries and populations displayed regression models with lower coefficients of determination including studies in France (R 2 varied between 0.32 and 0.47) (Tardivo et al 2011), Indonesia (R 2 = 75.3%) (Hidayat et al 2018), and India (R 2 = 75.5%) (Jagannathan et al (2011), as well as studies in subjects of Pakistani origin (R 2 = 0.33) (Kazmi et al 2019) and Egyptians (pulp volume of mandibular canines) (R 2 = 75.5%) (Elmoazen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The age coverage of the most study was young adult and children (71%) [11][12][13][14][15][16][17][18][19][20] . Only three studies which involved age range more than 25 years [21][22][23] . The youngest age of population involved in the studies was 4 years and the oldest was 73 years 11,22,23 .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
“…Only three studies which involved age range more than 25 years [21][22][23] . The youngest age of population involved in the studies was 4 years and the oldest was 73 years 11,22,23 . There is one study which did not specifically mentioned the age range information 24 .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes a reduction in the size of the pulp chamber space with age. [12][13][14] A study conducted by Arora et al 15 , showed that the decreasing size of the pulp chamber with age is due to the formation of secondary dentine. 15 Andrade et al 12 conducted a study on the correlation between age and sex based on pulp chamber volume.…”
Section: Introductionmentioning
confidence: 99%